Group structure and entitativity in group fitness: considering groupness at within- and between-group levels. Issue 6 (3rd June 2019) - Evans, M. Blair; Graupensperger, Scott; Benson, Alex J.; Eys, Mark; Hastings, Bryce; Gottschall, Jinger S.
Abstract: Objective: How can we distinguish between a collection of individuals exercising alongside one another from group that is exercising 'together'? This question is central to research on the extent that individuals perceive their fitness settings to entail core features of groups. To advance understanding of the nature of groupness and its implications in exercise, the current study (a) evaluated a brief measure of groupness and (b) examined the extent that groupness predicted perceptions of exertion and affect. Design: Participants included 633 exercisers ( M age = 33.92, SD = 11.05, 74% female) who completed surveys after group fitness classes ( k = 34). Main outcome measures: Groupness, affect, exertion, and group cohesion. Results: Exploratory structural equation modelling provided support for a two-factor solution reflecting entitativity and group structure as subdimensions of groupness. The groupness factors were differentially associated with theoretically relevant aspects of classes (e.g. synchronised movement), the individual (e.g. number of members interacted with), as well as group cohesion. Groupness also predicted perceived exertion and affect. Conclusion: Our research provides support for a brief measure of groupness, advances theory related to how individuals perceive exercise groups, and provides evidence regarding how broader experiences during exercise may relate to exercisers' perceptions of groupness.